IMPLEMENTASI TRI HITA KARANA DALAM PENGELOLAAN PURA TAMAN AYUN SEBAGAI DAYA TARIK WISATA - Ni Made Ayu Erna Tanu Ria Sari (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2019)
In improving the economic resilience of the Balinese people, especially in the field of tourism, in addition to seeing the potential that exists the government must also improve the social fabric of the local community, culture, and mentality. Therefore a strong concept is needed which becomes the basic foundation in the development of tourism in the form of Ecotourism. The foundation can be built in accordance with the local wisdom of the local community, or through a philosophical concept that is believed by the Hindu community in Bali that leads to a harmonious community life. One of the philosophical concepts of Hinduism which is also used as local wisdom is THK ("Tri Hita Karana"). Etymologically, the concept of Tri Hita Karana is Tri meaning three, Hita means prosperity, and Karana is the cause, consisting of parhyangan (spiritual environment), pawongan (social environment) and palemahan (natural environment). Broadly the concept of Tri Hita Karana can be interpreted as three harmonious relationships between humans and God, humans and other humans, and humans and the environment to achieve the safety and peace of the universe. Keywords: Tri Hita Karana, Taman Ayun Temple, Tourist Attraction